Instructional materials in communication arts II (English) based on geometry - Gamboa, Sabiniano G. (1977)
These instructional materials in Communication Arts (English) in the secondary level is specifically designed for team-teaching with the geometry teacher. This paper aimed to develop both the reading and language skills for communication competency of students taking geometry. The five lessons here are based on the discourse analysis of the textbook in geometry- Contemporary Geometry by Estrada et al. All of the lessons are integration of reading comprehension, vocabulary and structure.